Rome power & glory : the rise - Townsley, Graham; Fields, Ed; Westbrook, Joel; Coyote, Peter (Discovery Channel, 1998)
"Rome's dream of greatness was a prelude to a nightmare. It was not for another 100 years that the state would mature and commit to one enduring view of itself. It would be the army, more than any other force, that was destined to shape Rome's lasting identity"--Container.